Context-aware reuse in modelling instructional design and assembly of learning objects - Chong, Hwee-Reei; Lee, Chien-Sing (IEEE Xplore, 2006)
An evolutionary perspective of course design and development requires capturing, managing and reusing pedagogical knowledge in various contexts. This paper addresses the capture, management and reuse of two aspects of pedagogical knowledge in our OntoID authoring tool: instructional design knowledge and knowledge embedded in learning objects. Management and reuse are made possible through the use of software design patterns. Significance of the study lies in the Eclectic Instructional Design Builder pattern, which bridges the gap between behaviourist, cognitivist and constructivist learning approaches; the Case-based pattern which forms the basis for our case-based knowledge base, case-based search and modification of learning strategies and tasks to suit different contextual needs; and the Unified Content Model pattern which enables dynamic retrieval and assembly of parts of learning objects.